DESIGN & ANALYSIS FOR STRENGTH OF SCHOOL BUS SEAT TO AVOID THE FAILURE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Advanced manufacturing engineering is a move towards to build an object with the insertion of all technical features including sturdiness and safety. In automobile manufacturing approach, it can be a great opportunity to save life of inhabitant if safety parameters were intended successfully. Business commuter vehicles can carry several people at a time, and if accident happens, numerous people can die overall. These types of vehicle can have impact from different sides i.e. front, side, rear etc. Among these types of collisions impact of frontal collision is the most ruthless. In front impact traveler can get injured by hitting the seat structure mounted just next front to them. In order to design these seats properly to avoid such injuries, government also imposed some policies related to seat design. In order to overcome on such the compulsory regulations, accurately designed seat has to be sent to the government authorized organization to have the test certificate. Advanced simulation tools can also help out to improve the design .In this paper, simulating the H1, H2 test on bus seat to decide its bending strength and modifying the design to pass AUTOMOTIVE INDUSTRY STANDARD -023 test. The CAD geometry of 2 leg seat is made of using CATIA and is pre-processed by using HYPERMESH software. The simulation is carried out with LS-DYNA software to assess the seat to satisfy the requirements mentioned in Automotive industry standard ‘Automotive industry standard -023’. The result of the FEA analysis is correlated with the experimental outcome.